2009
DOI: 10.1246/cl.2009.770
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence and Electron Paramagnetic Resonance Studies of the Excited States of a UV Absorber, 2-Methylphenyl 2-Naphthoate

Abstract: Fluorescence, phosphorescence, and electron paramagnetic resonance spectra have been observed for the excited states of a new UV absorber, 2-methylphenyl 2-naphthoate (2-MPN), in ethanol at 77 K. The observed phosphorescence spectrum, phosphorescence lifetime, and zero-field splitting parameters of the lowest excited triplet (T1) state of 2-MPN revealed that the T1 state of 2-MPN can be regarded as a locally excited triplet state within naphthalene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It is especially important to determine the energy level of the lowest excited triplet (T 1 ) state of individual UV absorber because triplet−triplet energy transfer from a donor to an acceptor will occur between the UV absorbers. We have determined the energy levels of the T 1 states of UV absorbers by measuring the phosphorescence spectra in rigid solutions at 77 K and elucidated the nature of the T 1 states of the UV absorbers. …”
Section: Introductionmentioning
confidence: 99%
“…It is especially important to determine the energy level of the lowest excited triplet (T 1 ) state of individual UV absorber because triplet−triplet energy transfer from a donor to an acceptor will occur between the UV absorbers. We have determined the energy levels of the T 1 states of UV absorbers by measuring the phosphorescence spectra in rigid solutions at 77 K and elucidated the nature of the T 1 states of the UV absorbers. …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] It is important to determine the energy levels of the excited states of individual UV absorber because the energy transfer is one of the most important interactions between the UV absorbers. [12][13][14][15] Recently, it has been shown that the excited triplet state of the keto form is responsible for photodegradation of BM-DBM. 6 It is especially important to determine the energy levels of the lowest excited triplet (T 1 ) states of individual UV absorbers because, in general, triplet energy transfer will occur when the T 1 energy of the acceptor is equal to or lower than that of the donor.…”
Section: Introductionmentioning
confidence: 99%